Serum calprotectin (S100A8/A9) levels as a new potential biomarker of treatment response in Hodgkin lymphoma - TOPTAŞ, TAYFUR (WILEY, 2021)
Introduction Hodgkin lymphoma (HL) is unusual among malignancies, with inflammation playing such a prominent role in its pathogenesis. S100A8/A9 (calprotectin) is a heterodimeric protein, which has a role in the inflammatory response and oncogenesis. In this study in HL patients, the correlation between serum S100A8/A9 levels and treatment responses was investigated along with whether this marker is correlated with other inflammatory markers. Materials and Methods Thirty-three HL patients and 20 healthy volunteers were included. Demographic and clinical characteristics were recorded. Calprotectin levels were measured with Human S100A8/A9 Heterodimer Quantikine ELISA kit. Calprotectin levels were measured twice in patients, before and after treatment, and once in the control group. Treatment responses were evaluated with positron emission tomography-computed tomography (PET-CT). Results The mean age of patients was 44.3 +/- 18.1 (66.3% male). The median (IQR) values of S100A8/A9 before and after treatment in the patient group were 4.98 (2.6-7.8) and 1.87 (1.1-4.8)mu g/mL. Median (IQR) S100A8/A9 concentration in the control group was 1.41 (0.98-2.73)mu g/mL. In patients, pretreatment values were significantly higher than in controls (P < .001). However, median values of patients after treatment and controls were similar. Patient median S100A8/A9 levels were significantly lower post-treatment compared with pretreatment values (P = .001). When inflammatory markers were examined within groups, no relationship was found between markers. In ROC analysis, a S100A8/A9 cutoff value of >= 3.31 mu g/mL accurately discriminated end-of-treatment PET positivity (AUC = 0.78; 95% CI 0.58-0.98; accuracy = 76.2%). Conclusion S100A8/A9 may be a potential biomarker for treatment response in HL independent of inflammation. This is the first study to investigate and show this finding. However, further large-scale studies are still required.
Keywords: biomarker; calprotectin; Hodgkin lymphoma; A9; SUPPRESSOR-CELLS; EXPRESSION; DIFFERENTIATION; CARCINOMA; GROWTH; TARC